ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELANJA ONLINE MENGGUNAKAN MEDIA SOSIAL INSTAGRAM - Habib Kodhim Setiawan; Purwoko Purwoko (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
Consumers are currently given many choices in online shopping. The first social media created to socialize cyberspace, now increasingly equipped with business functions so that it can also be used as online shops. The high growth of Instagram social media users has made businessman also look to use this media for business. Therefore it is necessary to identify the factors that influence the user in finding information to do shopping through this Instagram social media. This study aims to test the UTAUT2 model in Instagram’s use behavior for online shopping. This research uses quantitative methods with an instrument in the form of a questionnaire. The population of this research is Instagram users who have ever shopped online in Indonesia, with the number of respondents who have shopped as many as 202. The analytical method in this study uses SEM-PLS. And the results of the study indicate that there are several significant factors in influencing Instagram's use behavior for online shopping, namely Facilitating Condition, Habit, Price value and Behavioral Intention..